Positive electrode material and preparation method and application thereof
By designing a multi-layer structure in the positive electrode material, and using the induction effect of the first shell layer and the second shell layer to promote the release of lattice oxygen, the problem of poor thermal stability of lithium nickel composite oxide and sodium nickel composite oxide is solved, and the problem of poor thermal stability of lithium nickel composite oxide is achieved. Higher thermal stability and safety performance.
Patent Information
- Application Number
- CN202310955157.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-14
AI Technical Summary
Lithium-nickel composite oxides and sodium-nickel composite oxides have poor thermal stability in thermal abuse and electrical abuse scenarios, which can easily lead to thermal runaway from the battery and limit their large-scale application.
A positive electrode material is designed, including a core, a first shell and a second shell. The core is A(Ni1-xMx)O2, the first shell is A(Ni1-xMx)1-aEaO2, and the second shell is a compound with Li-O and/or Na-O bonds. The first shell layer is doped by E element and arranged in a specific atomic structure, and the second shell layer is formed by Li-O and/or Na-O bonds, jointly promoting the release of lattice oxygen and improving thermal stability.
While taking into account the good intrinsic electrochemical properties, the thermal stability of the cathode material is significantly improved, peak heat exothermic, reduced the risk of thermal runaway, and improved the safety performance of the battery.
Smart Images

Figure CN119447203A_ABST
Abstract
Description
Technical Field
[0001] Embodiments of the present application relate to the technical field of batteries, and specifically to cathode materials, their preparation methods, and applications. Background Art
[0002] Lithium nickel composite oxides and sodium nickel composite oxides are expected to be widely used in batteries and energy storage systems due to their high energy density and good rate performance. However, the above materials have poor thermal stability in some scenarios (such as thermal abuse, electrical abuse, etc.). For example, they generate heat through side reactions with electrolytes and release lattice oxygen, and the concentrated release of heat can lead to thermal runaway of the battery, which severely restricts the large-scale application of the above materials.
[0003] To improve the thermal stability of the above materials, the industry chooses to coat a shell layer on the surface of the above materials or perform element doping on the whole material. However, the above solutions are relatively single. The surface shell layer generally inhibits side reactions by suppressing the contact between the material and the electrolyte, and the improvement effect on the thermal stability of the material is limited. Doping with some elements (such as Al) can fix the lattice oxygen of the material to improve thermal stability, but doping the whole material will affect some intrinsic electrochemical properties of the material while improving thermal stability, and local doping will also make the scope of action limited, basically only limited to improving the thermal stability of the doped area. Therefore, how to improve the thermal stability while maintaining the intrinsic electrochemical properties of the material is the common demand for solving the safety pain points of the above materials. Summary of the Invention
[0004] In view of this, embodiments of the present application provide a cathode material, its preparation method, and application. The cathode material has high thermal stability and high safety performance while taking into account good intrinsic electrochemical properties.
[0005] In a first aspect of the present application, a cathode material is provided, which includes a core and a first shell layer and a second shell layer sequentially coated on the surface of the core; the core includes A(Ni 1-x M x )O2, 0 < x < 1, where A is Li and / or Na, and M is at least one of Co, Mn, Nb, Ta, V, Mo, W, and Zr;
[0006] The first shell layer includes A(Ni 1-x M x ) 1-a E a O2, 0 < x < 1, 0 < a < 1, and E is at least one of Al and Mg;
[0007] The second shell layer includes a compound having Li—O and XO bonds, and / or a compound having Na—O and XO bonds; X is at least one of B, P and Si.
[0008] Under the thermal flooding environment, for the material near the first shell in the core, the E element in the first shell has a significant effect on the O 2- With strong polarization effect, and A(Ni 1-x M x ) 1-a E a The specific atomic arrangement structure of O2 makes the first shell have a first-type inductive effect on the lattice oxygen in the above-mentioned region, which can promote its escape; the second shell has Li-O bonds and / or Na-O bonds and XO bonds, which can form Li-OX bonds and / or Na-OX bonds, thereby further forming a polyanion structure, which has a second-type inductive effect on the lattice oxygen in the above-mentioned core region; therefore, under the dual effects of the first-type inductive effect and the second-type inductive effect, the binding ability of the atoms around the lattice oxygen to it is greatly weakened, so it can promote the release of lattice oxygen in the above-mentioned core region (that is, improve the release kinetics of lattice oxygen in the corresponding region of the core), and escape from the positive electrode material in the form of oxygen, so that the heat can be evacuated before the battery cell is further thermally runaway, suppressing the peak heat release caused by the positive electrode material, thereby reducing the total heat generation of the positive electrode material, and then improving the thermal stability of the positive electrode material. At the same time, the small-area doping of the first shell will hardly affect the intrinsic electrochemical properties of the positive electrode material. In addition, the second shell layer also has a physical barrier effect, preventing the electrolyte from reacting with the active components in the positive electrode material, which can reduce the risk of chain side reactions in the positive electrode material and improve the cycle performance of the positive electrode material at room temperature. Therefore, the positive electrode material provided in the embodiment of the present application can have high thermal stability and high safety performance while taking into account good intrinsic electrochemical performance.
[0009] In some embodiments of the present application, the thickness of the first shell layer is less than or equal to 10 nm. In this way, there is sufficient material of the first shell layer to induce the material in the corresponding region of the core to release lattice oxygen in advance, and the distance between the second shell layer and the core is more appropriate, which is conducive to the second type of induction effect.
[0010] In some embodiments of the present application, in the first shell, the content of the E element gradually decreases from the first shell toward the core. Further, the thickness of the first shell is less than or equal to 1 nm. The appropriate thickness can enable the inductive effects of the first shell and the second shell to be fully exerted.
[0011] In some embodiments of the present application, in the first shell layer, the content of element E first increases and then decreases in the direction from the first shell layer towards the inner core. Such a setting can increase the maximum action depth of the first type of induction effect of the first shell layer material.
[0012] In some embodiments of the present application, in the first shell layer, the distance from the peak position of the molar content of element E to the surface of the inner core is 50%-80% of the thickness of the first shell layer. A more appropriate peak position of the content of element E is conducive to the exertion of the first type of induction effect; at the same time, its action depth has a good overlap with the action depth of the second type of induction effect.
[0013] In some embodiments of the present application, 0 < a ≤ 0.1. This doping concentration can enable the first shell layer to have good electrochemical activity.
[0014] In some embodiments of the present application, any 1 μm 2 The thickness difference within the range is less than or equal to 6 nm. In this way, the second shell layer has high uniformity, so that on the circumferential length of the inner core, the second type of induction effect it receives is more uniform, which is conducive to the lattice oxygen in the corresponding area of the inner core being released from the cathode material in the form of oxygen in advance.
[0015] In some embodiments of the present application, any 1 μm 2 In the material of the second shell layer with an area of 1 nm - 5 nm in thickness, the molar content of element X is in the range greater than 0 to less than or equal to 13%. In this way, there is an appropriate amount of polyanion structure in the second shell layer, which can not only better achieve the second type of induction effect, but also has good ionic conductivity itself.
[0016] In some embodiments of the present application, the surface layer of the second shell layer includes a plurality of closely packed nanoparticles, and there are pores between adjacent nanoparticles, and the pore diameter of the pores is less than or equal to 1 nm. In this way, the second shell layer is relatively dense, can better isolate the electrolyte, and further reduce the risk of side reactions between the cathode material and the electrolyte.
[0017] In some embodiments of the present application, there is also a cross-composite layer between the first shell layer and the second shell layer. The cross-composite layer includes the compound having Li-O and X-O bonds and / or the compound having Na-O and X-O bonds, and element E. The existence of the cross-composite layer makes the combined effect of the first type of induction effect and the second type of induction effect more obvious, and is more conducive to reducing the total heat generation of the cathode material.
[0018] In some embodiments of the present application, the thickness of the cross-composite layer is less than or equal to 2 nm. In this way, it is conducive to controlling the deintercalation path length of the active ions in the cathode material within a more appropriate range.
[0019] In some embodiments of the present application, the A(Ni 1-x M x )O2 has a layered structure.
[0020] The second aspect of the embodiment of the present application provides a method for preparing a positive electrode material, which can be used to prepare the positive electrode material provided in the first aspect of the embodiment of the present application, comprising:
[0021] The substrate is placed in a reaction chamber filled with dry gas, and the first reaction raw material and the second reaction raw material are introduced. After atomic layer deposition, a positive electrode material is prepared; wherein the first reaction raw material includes an A element source, an X element source and an E element source; and the second reaction raw material includes an O element source.
[0022] The preparation method of the positive electrode material provided in the embodiment of the present application simultaneously generates the first shell layer and the second shell layer in situ on the surface of the substrate by the atomic layer deposition method, has strong process reliability, fully improves the controllability of the thickness and uniformity of the first shell layer and the second shell layer, and can ultimately obtain a positive electrode material with both good electrochemical performance and high thermal stability. At the same time, large-scale industrial production of positive electrode materials can be realized.
[0023] In some embodiments of the present application, when the first reaction raw material is introduced into the reaction chamber, the A element source, the X element source and the E element source are introduced alternately. In this way, it is more conducive to the full reaction of each material source.
[0024] In some embodiments of the present application, the reactants after the atomic layer deposition are placed in an oxygen environment for heat preservation. In this way, the E element can be further diffused toward the center of the substrate and form a gradient doping in the second shell layer, and the material of the second shell layer can be completely or partially transformed from an amorphous phase to a crystalline phase.
[0025] The third aspect of the embodiment of the present application provides a positive electrode sheet, including the positive electrode material provided in the first aspect of the embodiment of the present application, or the positive electrode material prepared by the preparation method provided in the second aspect. The positive electrode sheet can be a positive electrode sheet for a lithium ion battery, or a positive electrode sheet for a sodium ion battery.
[0026] The fourth aspect of the embodiment of the present application provides a secondary battery, including the positive electrode sheet and the negative electrode sheet provided in the third aspect of the embodiment of the present application, and a separator and an electrolyte located between the positive electrode sheet and the negative electrode sheet. The secondary battery has both good electrochemical performance and high safety performance, especially high energy density and low thermal runaway risk. The above-mentioned secondary battery can be a lithium secondary battery or a sodium secondary battery.
[0027] The fifth aspect of the embodiment of the present application provides an electric device, including the secondary battery provided by the fourth aspect of the embodiment of the present application. Since the secondary battery provided by the embodiment of the present application is used for power supply, the electric device has a good market prospect. In some embodiments of the present application, the above-mentioned electric device includes but is not limited to 3C electronic equipment, power vehicles, etc.
[0028] The sixth aspect of the embodiment of the present application provides an energy storage system, including the secondary battery provided by the fourth aspect of the embodiment of the present application. Due to the use of the secondary battery provided by the embodiment of the present application, the energy storage system can have good thermal stability and good safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A schematic diagram of the structure of a positive electrode material provided in one embodiment of the present application;
[0030] Figure 2 A schematic diagram of the structure of a positive electrode material provided in another embodiment of the present application;
[0031] Figure 3 A scanning electron microscope (SEM) photograph of a positive electrode material provided in one embodiment of the present application;
[0032] Figure 4 TEM photo of the positive electrode material provided in Example 1 of the present application;
[0033] Figure 5 TEM photo of the positive electrode material provided in Example 2 of the present application;
[0034] Fig. 6A DSC curves of the positive electrode materials of Example 1 and Comparative Example 2 of the present application in a closed electrolyte-containing system;
[0035] Figure 6B and Figure 6C The thermogravimetric curves of the positive electrode materials of Example 1 and Comparative Example 2 of the present application and the curves of the change of oxygen production with temperature thereof are respectively;
[0036] Fig. 7A DSC curves of the positive electrode materials of Example 2 and Comparative Example 2 of the present application in a closed electrolyte-containing system;
[0037] Figure 7B and Figure 7C The thermogravimetric curves of the positive electrode materials of Example 2 and Comparative Example 2 of the present application and the curves of the change of oxygen production with temperature thereof are respectively;
[0038] Figure 8 DSC curves of the positive electrode materials of Comparative Example 1 and Comparative Example 2 in a closed electrolyte-containing system;
[0039] Fig. 9A The TOF-SIMS (Time of Flight Secondary Ion Mass Spectrometry) test result curve of phosphorus element in the positive electrode material of Example 1 at different etching times;
[0040] Fig. 9B The TOF-SIMS test results of the aluminum element of the positive electrode material of Example 1 at different etching times;
[0041] Fig. 10A The TOF-SIMS test result curve of phosphorus element in the positive electrode material of Example 2 at different etching times;
[0042] Fig. 10B The TOF-SIMS test results of the aluminum element of the positive electrode material of Example 2 at different etching times;
[0043] Fig.11 The X-ray photoelectron spectroscopy (XPS) test results of the positive electrode material of Example 1;
[0044] Fig.12 The XPS test results of the positive electrode material of Example 2;
[0045] Fig.13 X-ray diffraction (XRD) spectra of the positive electrode materials of Example 1 and Example 2 and the positive electrode material of Comparative Example 2.
[0046] Description of the accompanying drawings: 100 - positive electrode material; 10 - inner core; 21 - first shell layer; 22 - second shell layer; 23 - cross-composite layer. DETAILED DESCRIPTION
[0047] To meet the market's high energy density requirements for batteries, lithium nickel composite oxides / sodium nickel composite oxides are expected to be widely used in secondary batteries and energy storage devices. However, the thermal runaway of batteries caused by the poor thermal stability of lithium nickel composite oxides / sodium nickel composite oxides is one of the main reasons hindering the large-scale application of the above materials. Taking the commonly used nickel cobalt manganese ternary cathode material (abbreviated as NCM) for lithium secondary batteries as an example, the high energy density characteristic of NCM is premised on sacrificing thermal stability. The higher the Ni content in the NCM material, the higher the energy density of the material, and the poorer the thermal stability and structural stability. During the thermal decomposition process of the NCM ternary material, phase changes will occur, and the phase change process is accompanied by the release of lattice oxygen, generating a large amount of heat. At the same time, the NCM material will also undergo side reactions with the electrolyte to generate free radicals, which will trigger a chain reaction to release heat. When the temperature of the battery cell increases rapidly within a short period of time, it will trigger thermal runaway of the cell and even spread to the entire battery, resulting in thermal runaway of the battery.
[0048] To solve the above problems, an embodiment of the present application provides a cathode material. Please refer to Figure 1 , Figure 1 which is a schematic structural diagram of the cathode material according to an embodiment of the present application. The cathode material 100 includes a core 10 and a first shell layer 21 and a second shell layer 22 sequentially coated on the surface of the core 10; the core 10 includes A(Ni 1-x M x )O2, wherein A is Li and / or Na, and M is at least one of Co, Mn, Nb, Ta, V, Mo, W, and Zr;
[0049] The first shell layer 21 includes A(Ni 1-x M x ) 1-a E a O2, 0 < x < 1, 0 < a < 1, and E is at least one of Al and Mg;
[0050] The second shell layer 22 includes a compound having Li-O and X-O bonds, and / or a compound having Na-O and X-O bonds; X is at least one of B, P, and Si.
[0051] Exemplarily, the above cathode material 100 is a cathode material 100 for a lithium ion battery. The above core includes Li(Ni 1- x M x )O2. Then, the second shell layer 22 includes a compound having Li-O bonds and X-O bonds; when the core material is in Li(Ni 1-x M x)O2 is doped with Na at the Li position, the second shell 22 includes a compound having a Li-O bond and an XO bond, and may also include a compound having a Li-O and / or Na-O bond and an XO bond. Similarly, when the positive electrode material 100 is a positive electrode material 100 for a sodium ion battery, the core includes Na(Ni 1-x M x )O2, then, the second shell 22 includes compounds having Na-O bonds and XO bonds; on this basis, when the core material Na(Ni 1-x M x )When the Na position of O2 is also doped with Li, the second shell layer 22 may also include a compound having a Li—O bond and an XO bond.
[0052] The first shell layer 21 includes A(NiM) 1-x E x O2, E ions (specifically Al 3+ Mg 2+ ) for O in the above kernel region 2- It has a strong polarizing effect. In addition, the components of the first shell 21 are essentially E elements doped at the transition metal position in the material of the inner core, and have a specific atomic arrangement structure. When the positive electrode material 100 is heated (in a thermal flooding environment), the material of the first shell 21 has a first-class inductive effect on the material in the inner core near the first shell 21 region, which can promote the release of lattice oxygen of the material in the corresponding region of the inner core, improve the oxygen release kinetics of the corresponding region of the inner core, and then increase the oxygen release amount in the corresponding region of the inner core. Furthermore, compared with the overall doping in the prior art, the small-area element doping in the positive electrode material 100 of the embodiment of the present application will hardly affect the intrinsic electrochemical properties of the material, so the positive electrode material 100 also has a higher energy density. In addition, the above-mentioned E ion doping in A(Ni 1-x M x )O2 can also fix the lattice oxygen in the first shell material, inhibit the cation mixing of the first shell 21, and at the same time improve the thermal stability and cycle performance of the material in the first shell 21. Fig.13 The positive electrode material 100 and LiNi provided in the two embodiments of the present application 0.836 Co 0.104 Mn 0.06 From the XRD spectrum of O2 (equivalent to the core of the positive electrode material 100 ), the small area doping of the E element does not significantly change the crystal structure of the positive electrode material 100 .
[0053] The compound having Li-O bonds and / or Na-O bonds and XO bonds in the second shell 22 can form Li-OX bonds and / or Na-OX bonds, thereby further forming a polyanion structure. When heated, it has a second type of inductive effect on the lattice oxygen in the area near the second shell 22 in the inner core 10. Under the cooperation of the first type of inductive effect from the first shell 21, the binding ability of the atoms around the lattice oxygen in the material of the above inner core area is greatly reduced, making it easier for the lattice oxygen to escape, improving its oxygen release kinetics, and increasing the amount of oxygen released, thereby dissipating heat before the battery cell further runs away from heat, inhibiting the peak heat release caused by the positive electrode material 100, thereby reducing the total heat generation of the positive electrode material 100, and further improving the thermal stability of the positive electrode material 100, controlling and slowing down the heat spread in the battery, and improving the safety performance of the battery. Furthermore, the compound having a Li-O bond and an XO bond, and / or the compound having a Na-O bond and an XO bond, has a high ionic conductivity, which can improve the active ion extraction / insertion rate at the surface of the positive electrode material 100, and is beneficial to the rate performance of the battery. In addition, the second shell layer 22, as the surface layer of the positive electrode material 100 particles, can form a physical barrier with the electrolyte, hindering the electrolyte from reacting with the active components in the positive electrode material 100, and at the same time, can inhibit the material surface damage and electrical performance damage caused by the side reaction between the electrolyte and the highly delithiated positive electrode material 100 at room temperature, thereby improving the room temperature cycle performance of the battery.
[0054] Fig. 6A , Fig. 7A This is a DSC test curve of the positive electrode material 100 in a closed electrolyte system. It can be seen that the positive electrode material 100 provided in the embodiment of the present application has a total heat release during the test process that is less than that of the positive electrode material 100 in the prior art (equivalent to the inner core without the first shell layer 21 and the second shell layer 22).
[0055] It should be further explained that, from the inner core surface to the inner core center, when the inner core region with a depth of H1 (H1>0) is subjected to double induction, the material in this region can increase the oxygen release; at this time, the inner core material in the region with a depth of H1+h (h>0) will be affected by the above reaction, and may also increase the oxygen release, thereby promoting more lattice oxygen pre-decomposition in the inner core, further dispersing and suppressing the peak heat release caused by the positive electrode material 100.
[0056] See also Figure 6B , Figure 7B, the weight loss curve of the positive electrode material 100 provided in the embodiment of the present application as a function of temperature, in the range of 200°C-300°C, the weight loss rate of the positive electrode material 100 provided in the embodiment of the present application is significantly higher than that of the positive electrode material 100 in the prior art, indicating that more lattice oxygen in the positive electrode material 100 provided in the embodiment of the present application is released in this temperature range, making the weight loss rate of the positive electrode material 100 higher; correspondingly.
[0057] In addition, the lattice oxygen is in the form of non-stable free oxygen when it escapes from the unit cell, but these free oxygen will react with each other to generate oxygen in the process of passing through the first shell layer 21 and the second shell layer 22. Therefore, the lattice oxygen finally escapes from the positive electrode material 100 in the form of oxygen. In this way, it can be prevented that the free oxygen further reacts with the electrolyte to cause heat generation. Figure 6C as well as Figure 7C The oxygen production of the positive electrode material 100 provided in the embodiment of the present application in the range of 200° C.-250° C. is significantly higher than that of the materials in the prior art.
[0058] In summary, the positive electrode material 100 can improve thermal stability while taking into account electrochemical performance.
[0059] In the embodiments of the present application, time of flight secondary ion mass spectrometry (TOF-SIMS) or X-ray photoelectron spectroscopy (XPS) can be used to characterize the presence of Li-O bonds, Na-O bonds and XO bonds.
[0060] In the embodiments of the present application, Raman spectra may be used to characterize the doping sites of the E element.
[0061] In the embodiment of the present application, the M element in the core and the first shell 21 is independently selected from at least one of Co, Mn, Nb, Ta, V, Mo, W and Zr. The M element in the core and the M element in the first shell 21 may be completely the same or not completely the same. Exemplarily, the value of x may be 0.1, 0.12, 0.15, 0.20, 0.30, 0.40, 0.50, 0.60, etc. Specifically, taking the positive electrode material 100 for lithium-ion batteries as an example, the material of the core includes but is not limited to LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8Co 0.1 Mn 0.1 O2 (NCM811), etc. Correspondingly, when the material of the core is NCM811, the material of the first shell 21 can be but is not limited to Li (Ni 0.8 Co 0.1 Mn 0.1 ) 1-x E x O2; Specifically, the value of a can be, but is not limited to, 0.001, 0.005, 0.01, 0.02, 0.05, 0.08, 0.09, etc. Similarly, when the core material is other materials, the material of the first shell 21 can be analogized according to the above principles, which will not be repeated here. For example, taking the positive electrode material 100 for sodium ion batteries as an example, the material of the core includes, but is not limited to, NaNi 0.5 Mn 0.5 O2、NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 For the positive electrode material 100 for a sodium ion battery, the material of the first shell layer 21 is also analogous to the case of the positive electrode material 100 for a lithium ion battery, and will not be described in detail here.
[0062] In some embodiments of the present application, the thickness of the first shell 21 is less than or equal to 10nm. Specifically, the thickness of the first shell can be 0.1nm, 0.2nm, 0.3nm, 0.4nm, 0.5nm, 0.6nm, 0.7nm, 0.8nm, 0.9nm, 1nm, 2nm, 5nm, 8nm, 10nm, etc. The thickness of the first shell 21 is controlled within the above range, so that there is a sufficient amount of material to induce the release of lattice oxygen in the corresponding area of the core, and the action distance of the second inductive effect of the second shell 22 material is controlled within a suitable range, which is conducive to the dual inductive effect and the release of the aforementioned lattice oxygen. In addition, its proportion in the positive electrode material 100 is also suitable, which is conducive to the intrinsic electrochemical performance of the positive electrode material 100. The thicker the first shell 21 is, the more obvious its first type of inductive effect is, which may be beneficial to further reduce the total heat generation of the positive electrode material 100, but the distance of its inductive effect has an upper limit, and blindly increasing the thickness of the first shell 21 will not blindly increase the depth of the active area in the core that can promote the release of lattice oxygen. In the embodiment of the present application, TOF-SIMS can be used to characterize the thickness of the first shell 21 by changing the element content with depth.
[0063] In some embodiments of the present application, in the first shell 21, the content of the E element gradually decreases from the first shell 21 toward the core. 1-x M x ) 1-a E aThe value of a in O2 gradually decreases from the first shell 21 toward the core. Specifically, the content of the E element (the value of a) in the first shell 21 can be linearly reduced from the first shell 21 toward the core, or it can be nonlinearly reduced. At this time, further, the thickness of the first shell 21 is ≤1nm. It can be understood that the region with a high E element doping concentration (larger a value) in the first shell 21 has a stronger effect of inducing lattice oxygen release. At this time, the thickness of the first shell 21 is controlled to be smaller, which is beneficial to exert the inductive effect of the first shell 21 material in the above-mentioned region, and also to increase the depth of the second type of inductive effect of the second shell 22 material in the core, enhance its inductive effect, and under the synergistic effect of the two, it is more conducive to reducing the total heat generation of the positive electrode material 100 in a thermal flooding environment. Specifically, at this time, the thickness of the first shell 21 can be 0.1nm, 0.2nm, 0.3nm, 0.4nm, 0.5nm, 0.6nm, 0.7nm, 0.8nm, 0.9nm, 1nm, etc.
[0064] In some embodiments of the present application, in the first shell 21, the content of the E element first increases and then decreases from the first shell 21 toward the core. 1-x M x ) 1-a E a The value of a in O2 increases first and then decreases from the first shell 21 toward the inner core. In this way, it is equivalent to pushing the maximum depth of the first type of inductive effect toward the inner core by a distance, which is beneficial to the inductive effect of the material of the first shell 21. Specifically, at this time, the content of the E element (the value of a) in the first shell 21 can change linearly with the thickness direction of the first shell 21, or it can change nonlinearly.
[0065] In some embodiments of the present application, in the direction from the first shell layer 21 towards the inner core, the content of element E first increases and then decreases. At this time, the thickness of the first shell layer 21 is in the range of 1 nm - 10 nm. Specifically, the thickness of the first shell layer 21 can be 1 nm, 1.5 nm, 2.0 nm, 2.5 nm, 3.0 nm, 3.5 nm, 4.0 nm, 4.5 nm, 5.0 nm, 5.5 nm, 6.0 nm, 6.5 nm, 7.0 nm, 7.5 nm, 8.0 nm, 8.5 nm, 9.0 nm, 9.5 nm, etc. At this time, in some specific embodiments, along the thickness direction of the first shell layer 21, the distance from the position of the peak content of element E in the first shell layer 21 (i.e., the position of the maximum value of a) to the surface of the inner core is 50% - 80% of the thickness of the first shell layer. Specifically, the distance from the position of the peak content of element E in the first shell layer 21 to the surface of the inner core can be specifically 50.0%, 52.5%, 55.0%, 57.5%, 60.0%, 62.5%, 65.0%, 67.5%, 70.0%, 72.5%, 75.0%, 77.5%, 80.0%, etc. In this way, it is beneficial to exert the first type of induction effect, and at the same time, its action depth has a good overlap with the action depth of the second type of induction effect. In the embodiments of the present application, TOF - SIMS can be used to characterize the position of the peak content of element E from the surface of the inner core.
[0066] In some embodiments of the present application, 0 < a ≤ 0.1. That is, the molar content of element E in the first shell layer 21 is greater than 0 and less than or equal to 10%. Controlling the value of a (the doping amount of element E) within the above range can achieve a good first type of induction effect in the first shell layer 21 without losing the electrochemical activity of the first shell layer 21; at the same time, it can also make the lattice oxygen in the first shell layer 21 be better fixed, prevent cation mixing, be beneficial to the insertion and extraction of active ions in the first shell layer 21, and be beneficial to the rate of active ions in the inner core when passing through the first shell layer 21. Specifically, the value of a can be specifically 0.0001, 0.0005, 0.001, 0.005, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, etc. In some specific embodiments, 0.001 ≤ a ≤ 0.1. In the embodiments of the present application, TOF - SIMS or XPS can be used to characterize the molar content of element E.
[0067] In some embodiments of the present application, for any 1 μm of the second shell layer 22 2 the thickness difference within the range is less than or equal to 6 nm. That is, for any 1 μm of the second shell layer 22 2In the range: the maximum thickness of the second shell layer 22 - the minimum thickness of the second shell layer 22 ≤ 6nm. In this way, the thickness of the second shell layer 22 is relatively uniform everywhere, so that in the positive electrode material 100, the second type of induction effect is relatively uniform everywhere on the circumference of the core, which is beneficial to the release of lattice oxygen in the corresponding area of the core, and further to improve the thermal stability of the positive electrode material 100. Specifically, any 1μm thickness of the second shell layer 22 2 The thickness difference within the range can be 0, 0.5nm, 1.0nm, 1.5nm, 2.0nm, 2.5nm, 3.0nm, 3.5nm, 4.0nm, 4.5nm, 5.0nm, 5.5nm, 6.0nm, etc.
[0068] In some embodiments of the present application, any 1 μm of the second shell layer 22 2 The thickness within the range is in the range of 2nm-10nm. The thickness of the second shell 22 is controlled within the above range, and an appropriate amount of the material of the second shell 22 can exert its second type of induction effect on the core material, thereby facilitating the release of lattice oxygen in the material in the corresponding area of the core. At the same time, the second shell 22 has a suitable thickness, which is conducive to controlling the deintercalation path of the active ions within a suitable range, and has sufficient path length to convert the oxygen free radicals released from the core into oxygen, and then release it to the outside of the positive electrode material 100; the thickness of the second shell 22 is relatively suitable and evenly distributed, which is also conducive to its isolation from the electrolyte to avoid causing more side reactions. Specifically, any 1μm of the second shell 22 2 The thickness within the range may specifically be 2.0 nm, 2.5 nm, 3.0 nm, 3.5 nm, 4.0 nm, 4.5 nm, 5.0 nm, 5.5 nm, 6.0 nm, 6.5 nm, 7.0 nm, 7.5 nm, 8.0 nm, 8.5 nm, 9.0 nm, 9.5 nm, 10.0 nm, etc.
[0069] In some embodiments of the present application, any 1 μm 2 In the material of the second shell layer 22 with an area of 1 nm to a thickness of 5 nm, the molar content of the X element is in the range of greater than 0 to less than or equal to 13%. 2In the material of the second shell layer 22 with an area of 1 nm - 5 nm in thickness, the molar content of element X is denoted as b, where 0 < b ≤ 13%. In some specific embodiments of the embodiments of the present application, 0.1% ≤ b ≤ 13%. Controlling the molar content of element X within the above range enables an appropriate amount of polyanion structure in the second shell layer 22, so as to better achieve the second type of induction effect on the material in the corresponding region of the inner core, thereby facilitating the release of the above lattice oxygen; furthermore, it also helps to ensure that the ionic conductivity of the material of the second shell layer 22 is good, which is beneficial to the rate performance of the positive electrode material 100. Specifically, the above b can specifically be 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, 2.%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, etc.
[0070] In some embodiments of the present application, the material of the second shell layer 22 is in an amorphous phase. In some embodiments, the material of the second shell layer 22 is in a crystalline phase. In other embodiments, the material of the second shell layer 22 includes a crystalline phase and an amorphous phase. Those skilled in the art can make a choice according to actual application needs.
[0071] In some embodiments of the present application, the surface of the second shell layer 22 includes a plurality of closely packed nanoparticles. During the preparation process of the positive electrode material 100, if the atomic layer deposition method is used to prepare the first shell layer 21 and the second shell layer 22, it may cause nanoparticles to be arranged on the surface of the second shell layer 22, and pores will be formed between adjacent nanoparticles. In some embodiments of the present application, there are pores between adjacent nanoparticles, and the pore diameter of the pores is less than or equal to 1 nm. Controlling the pore diameter of the above pores within the above range can improve the denseness of the second shell layer 22, thereby enhancing the effect of the second shell layer 22 as a physical barrier and further reducing the risk of side reactions between the positive electrode material 100 and the electrolyte. Specifically, the pore diameter of the above pores can specifically be 0.05 nm, 0.1 nm, 0.2 nm, 0.3 nm, 0.4 nm, 0.5 nm, 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, 1.0 nm, etc. In some other specific embodiments of the present application, there are no pores on the surface layer of the second shell layer 22. At this time, it is more conducive to ensuring the denseness of the second shell layer 22, thereby further reducing the risk of side reactions between the positive electrode material 100 and the electrolyte.
[0072] In the embodiment of the present application, the surface of the second shell layer 22 is densely packed with a plurality of nanoparticles. The second shell layer 22 may include a dense bottom layer, and the bottom layer is covered with a single layer of nanoparticles; or the bottom layer may be arranged with two or more layers of nanoparticles; or a part of the bottom layer may be covered with a single layer of nanoparticles, and another part of the bottom layer may be arranged with two or more layers of nanoparticles; but the invention is not limited thereto. For specific morphology, please refer to Figure 3 , Figure 3 This is a SEM photo of the positive electrode material 100 of one embodiment of the present application. In the embodiment of the present application, the particle size of the above-mentioned nanoparticles can be less than or equal to 10nm, less than or equal to 100nm, or less than or equal to 500nm, but not limited thereto. In the embodiment of the present application, the shape of the nanoparticles can be spherical, quasi-spherical, flaky, etc., but not limited thereto.
[0073] In some implementations of this application, please see Figure 2 There is also a cross-composite layer 23 between the first shell 21 and the second shell 22, and the cross-composite layer 23 includes compounds with Li-O bonds and XO bonds and / or compounds with Na-O bonds and XO bonds, and E elements. In the cross-composite layer 23, the E element tends to be in the Li position or the Na position, and can form a configuration similar to a tetrahedral structure with some compounds containing Li-OX bonds and / or Na-OX bonds, and has a first-type inductive effect on the materials in the corresponding area of the inner core; the other part of the compounds with Li-O bonds and XO bonds and / or compounds with Na-O bonds and XO bonds has a second-type inductive effect on the materials in the corresponding area of the inner core. Therefore, at this time, the composite effect of the two types of inductive effects is more obvious, so it is more conducive to inducing the release of lattice oxygen. In some specific embodiments of the present application, the composite cross-layer has both the materials of the first shell 21 and the materials of the second shell 22. In some specific embodiments of the present application, chemical bonds can be formed between the E element in the region of the composite cross layer close to the second shell layer 22 and the compounds having Li-O bonds and XO bonds in the second shell layer 22, and / or the compounds having Na-O bonds and XO bonds, thereby improving the interfacial bonding force between the first shell layer 21 and the composite cross layer, which is beneficial to improving the structural stability of the positive electrode material 100.
[0074] In some embodiments of the present application, the thickness of the cross-composite layer 23 is less than or equal to 2 nm. The thickness of the cross-composite layer 23 being less than or equal to 2 nm means that along the direction from the inner core towards the first shell layer 21, the thickness extending towards the second shell layer 22 from the surface of the first shell layer 21 is less than or equal to 2 nm. Controlling the thickness of the cross-composite layer 23 within the above range, its presence will not affect the induction effect of the second shell layer 22 on the material in the corresponding area of the inner core under overheating conditions, and at the same time, it is also beneficial to control the diffusion path of active ions in the positive electrode material 100 within a relatively short range. In some specific embodiments, due to the preparation method, there may be a small amount of element E in the second shell layer 22. In some specific embodiments, the thickness of the cross-composite layer 23 is 0.1 nm - 2 nm. Specifically, the thickness of the cross-composite layer 23 can specifically be 0.1 nm, 0.2 nm, 0.3 nm, 0.4 nm, 0.5 nm, 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, 1.0 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm, 1.5 nm, 1.6 nm, 1.7 nm, 1.8 nm, 1.9 nm, etc.
[0075] In some embodiments of the present application, the material of the inner core has a layered structure. For the lithium-ion positive electrode material 100, its layered structure means that the inner core material can be divided into a Li layer and a transition metal oxide layer; for the sodium-ion positive electrode material 100, its layered structure includes a transition metal layer, and sodium ions are located between the layers of the transition metal layer, forming an alternating layered structure.
[0076] In some embodiments of the present application, the inner core material includes A(Ni 1-x M x )O2, where 0 < x ≤ 0.2. Specifically, the value of x can specifically be 0.0001, 0.0005, 0.001, 0.005, 0.01, 0.02, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.19, 0.20, etc. Especially for Li(Ni 1-x M x )O2, the molar content of Ni element in the inner core material is greater than or equal to 80%. For example, 80% - 87%, etc. Increasing the molar content of Ni in the inner core can improve the capacity of the positive electrode material 100, so the energy density of the final battery can be improved.
[0077] In the embodiments of the present application, the D of the positive electrode material 100 VThe particle size of Dv50 of the positive electrode material 100 is in the range of 2μm to 20μm. Those skilled in the art can select according to the actual application needs. Specifically, the Dv50 particle size of the positive electrode material 100 can be 2μm, 3μm, 4μm, 5μm, 8μm, 10μm, 12μm, 15μm, 18μm, 20μm. Among them, Dv50 refers to the particle size corresponding to 50% of the volume distribution of the positive electrode material 100, which can be measured by a laser particle size analyzer.
[0078] Accordingly, the embodiment of the present application further provides a method for preparing a positive electrode material, which can be used to prepare the positive electrode material 100, comprising:
[0079] The substrate is placed in a reaction chamber filled with dry gas, and the first reaction raw material and the second reaction raw material are introduced; wherein the first reaction raw material includes an A element source, an X element source and an E element source; the E element includes at least one of Al and Mg; the X element includes at least one of B, P and Si; the second reaction raw material includes an O element source; after atomic layer deposition (ALD), a positive electrode material is prepared. Further, in some specific embodiments, the A element in the A element source is the same as the A element in the substrate. It can be understood that when preparing a positive electrode material for a lithium secondary battery, the A element in the above-mentioned substrate includes Li, then the A element source can be a lithium element source; further, when the material in the substrate is also doped with Na at its Li position, the A element source can include a Li element source and / or a sodium element source. Similarly, when preparing a positive electrode material for a sodium secondary battery, an analogy can be made according to the above principles, which will not be repeated here.
[0080] The substrate is treated by the above process, and the first shell and the second shell can be formed by in-situ reaction at the same time. In the obtained positive electrode material, the compatibility between the first shell and the core is high, and the compatibility between the first shell and the second shell is high, and the interface bonding between the two is good. Specifically, the first reaction raw material is adsorbed on the surface of the substrate, and the second reaction raw material reacts chemically with the first reaction raw material adsorbed on the surface of the substrate, generating the second shell and by-products on the surface of the substrate, and making the E element in the E element source spontaneously diffuse and doped into the material of the surface layer of the substrate to achieve small-area doping, so that the substrate of the surface layer is transformed into the first shell, and the internal substrate is transformed into the core. Due to the self-limiting characteristics of ALD, when the first reaction raw material is completely reacted, the above chemical reaction will automatically terminate, and the residual second reaction raw material and by-products can be extracted from the system, and the thickness of the atomic level can be regulated. Therefore, the above process can also flexibly and accurately regulate the thickness of the first shell and the second shell, and can also take into account the uniformity of the first shell and the second shell, so as to improve the comprehensive performance of the positive electrode material.
[0081] In some embodiments of the present application, since the positive electrode material is prepared by the above method, a small amount of E element still exists in the second shell layer.
[0082] In the embodiment of the present application, the reaction chamber is a reaction chamber of an atomic layer deposition device. The dry gas filled in the reaction chamber may be dry air.
[0083] In the embodiment of the present application, the first reaction raw material and the second reaction raw material are both in gaseous state.
[0084] In some embodiments of the present application, the above preparation method can be further broken down into steps S01 to S04:
[0085] Step S01, placing the substrate in a reaction chamber filled with dry gas, and heating it to a first preset temperature; in some specific embodiments, the first preset temperature is in the range of 200°C-300°C. Specifically, the first preset temperature can be 200°C, 210°C, 220°C, 250°C, 260°C, 280°C, 300°C, etc.
[0086] Step S02, introducing the first reaction raw material into the reaction chamber, and after a first preset time, introducing an inert gas into the reaction chamber to clean the reaction chamber, so as to remove the first reaction raw material that has not been adsorbed on the surface of the substrate;
[0087] Step S03, introducing the second reaction raw material into the reaction chamber, and after a second preset time, introducing an inert gas to clean the reaction chamber to remove excess second reaction raw material and by-products.
[0088] Furthermore, the embodiment of the present application also includes step S04: repeat the above steps S02-S03 several times to obtain a positive electrode material. The thickness of the second shell layer can be adjusted by controlling the above number of repetitions (number of deposition turns), and in particular, thickness regulation at the atomic level can be achieved. The above number of repetitions may be ≥10 times, and in some specific embodiments, may be ≥15 times, for example, 16-50 times. Specifically, the above number of repetitions may be 16, 20, 22, 25, 28, 30, 32, 35, 38, 40, 42, 45, 48 times, etc. It can be selected according to actual application requirements.
[0089] In some embodiments of the present application, step S05 is also included: it also includes placing the reactants after the atomic layer deposition in an oxygen environment for heat preservation treatment. The heat preservation treatment can make the material of the second shell layer completely or partially transformed from the amorphous phase to the crystalline phase. In addition, it can further promote the E element to continue to diffuse and dope toward the center of the substrate, increase the thickness of the first shell layer, and form a gradient doping in the first shell layer. Specifically, after the heat preservation treatment, the thickness of the first shell layer in the positive electrode material can be controlled within the range of 1nm-10nm, and along the direction of the first shell layer pointing to the inner core, the content of the E element in the first shell layer first increases and then decreases. In some specific embodiments, the thickness of the first shell layer is 7nm-9nm. In some specific embodiments, the peak position of the E element content in the first shell layer is 50%-80% of the thickness of the first shell layer from the surface of the inner core.
[0090] In some embodiments of the present application, the reactants after the atomic layer deposition can be transferred to a tubular reactor, subjected to heat preservation treatment in an oxygen environment, and cooled to obtain a positive electrode material. In the embodiment of the present application, the heat preservation temperature of the heat preservation treatment can be higher than the aforementioned second preset reaction temperature. In the embodiment of the present application, the above cooling can be natural cooling.
[0091] In some specific embodiments of the present application, the conditions of the above-mentioned heat preservation treatment are: heat preservation at 300℃-600℃ for 2h-6h. Specifically, the temperature of the heat preservation treatment can be 300℃, 325℃, 350℃, 375℃, 400℃, 425℃, 450℃, 475℃, 500℃, 525℃, 550℃, 575℃, etc.; the heat preservation time of the heat preservation treatment can be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, etc. The above-mentioned heat preservation temperature is conducive to the diffusion of the E element toward the center of the substrate, and is also conducive to the crystallization of the material of the second shell layer, and will not damage the structure of the core material. In some specific embodiments of the present application, during the heat preservation treatment, the heating rate is in the range of 1℃ / min-10℃ / min. In this way, it is conducive to the further diffusion of the E element, the crystallization of the second shell material, and the regulation of the crystal structure. Specifically, the above-mentioned heating rate can be 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, etc.
[0092] In some embodiments of the present application, in step S02, when the first reaction raw material is introduced into the reaction chamber, the A element source, the X element source and the E element source are introduced into the reaction chamber alternately. Specifically, each time the first reaction raw material is introduced, it can be in the order of A element source / X element source / E element source, or in the order of E element source / X element source / A element source, X element source / E element source / A element source, but is not limited thereto; when it is necessary to repeat step S02-step S03, the order of introducing the above-mentioned element sources may be different when the first reaction raw material is introduced and when the first reaction raw material is introduced for the i-th time (i is a positive integer greater than 1).
[0093] In some specific embodiments of the present application, step S02 may include: passing 3-5 times of A element source, 1-3 times of X element source and 3-5 times of E element source into the reaction chamber, without making specific restrictions on the order of passing the above-mentioned element sources, and the same element source may be passed twice in a row. In this way, it is beneficial for the substances to fully react to generate a uniform second shell layer, and it is also beneficial for the doping of E element in the surface layer of the substrate. In the implementation mode of the present application, the time of passing through different element sources and the flow rate of passing through may be the same or different. It can be selected according to the actual reaction characteristics and material characteristics. In some specific embodiments, the duration of a single passing through of the A element source can be 200ms-400ms, the time of a single passing through of the X element source can be 1100ms-1300ms, and the time of a single passing through of the E element source can be 200ms-400ms, but it is not limited thereto.
[0094] In the embodiment of the present application, the A element source includes at least one of the Li element source and the Na element source. Among them, the Li element source includes but is not limited to at least one of lithium tert-butoxide and cyclopentadienyl lithium. The Na element source includes but is not limited to at least one of sodium ethoxide and sodium tert-butoxide. The X element source includes at least one of the P element source, the Si element source, and the B element source. Among them, the P element source includes but is not limited to at least one of triethyl phosphate, trimethyl phosphate, tri(dimethylamino)phosphine, and diethyl phosphate. The Si element source includes but is not limited to at least one of hexamethylsilanediamine, bis(diethylamino)silane, and tri(dimethylamino)silane. The B element source includes but is not limited to at least one of triethyl borate and triethyl boron. The E element source includes but is not limited to at least one of the Al element source, the Mg element source, and the Ti element source. Among them, the Al element source includes but is not limited to organic aluminum compounds, and organic aluminum compounds include but are not limited to at least one of trimethyl aluminum, triethyl aluminum, and aluminum sec-butoxide. The Mg element source includes but is not limited to organic magnesium compounds, which include but are not limited to at least one of bis(pentamethylcyclopentene)magnesium, magnesium acetylacetonate octahydrate, bis(n-propylcyclopentadienyl)magnesium, and 1,1,1-trifluoroacetylacetonate magnesium. The Ti element source includes but is not limited to organic titanium compounds, which include but are not limited to at least one of titanium tetrachloride, tetrakis(ethylmethylamino)titanium, tetrakis(dimethylamino)titanium, and isopropyl titanate.
[0095] In some embodiments of the present application, in step S03, the above-mentioned O element source includes but is not limited to O3 or H2O.
[0096] In some implementations of the present application, in step S03, the duration of a single introduction of the O element source may be 100ms-300ms, and the number of introductions may be 2-5 times.
[0097] In the embodiment of the present application, the substrate is the same as the material of the core of the positive electrode material. In other words, the substrate comprises A(Ni 1-x M x )O2, wherein A is Li and / or Na, and M is at least one of Co, Mn, Nb, Ta, V, Mo, W and Zr.
[0098] In some embodiments of the present application, taking lithium-ion battery materials as an example, the substrates include but are not limited to LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1O2 (NCM811), etc. Further, in the lithium ion battery material, the molar content of Ni element in the substrate is greater than or equal to 80%.
[0099] The present application also provides a positive electrode sheet for a battery, comprising a current collector and a positive electrode active material layer disposed on at least one side of the current collector; the positive electrode active material layer comprises the positive electrode material 100 provided in the present application. In some embodiments, the positive electrode active material layer comprises a positive electrode active material and a binder. In some specific embodiments, the positive electrode active material layer further comprises a conductive agent.
[0100] The positive electrode current collector includes but is not limited to metal foil or alloy foil. Specifically, when the battery is a lithium secondary battery, the metal foil may be aluminum foil, or carbon-coated aluminum foil. Specifically, when the battery is a sodium secondary battery, the metal foil may be but is not limited to aluminum foil or carbon-coated aluminum foil.
[0101] In the embodiment of the present application, there is no special restriction on the binder and the conductive agent in the positive electrode active material, and it can be any known binder and conductive agent for positive electrode sheets in the field. Exemplarily, the binder includes but is not limited to at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyacrylate, polyacrylamide (PAM), polyimide (PI), etc. The conductive agent may specifically include but is not limited to at least one of acetylene black (AB), Ketjen black, Supper P conductive carbon black, graphite, graphene, carbon nanotubes, carbon fibers, etc.
[0102] The embodiment of the present application also provides a secondary battery, which includes the positive electrode plate and the negative electrode plate provided in the embodiment of the present application, the electrolyte and the separator located between the positive electrode plate and the negative electrode plate, and the corresponding connecting accessories and circuits. The secondary battery can be a lithium secondary battery or a sodium secondary battery. The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector. The negative electrode plate, the separator and the electrolyte can be any negative electrode plate, the separator and the electrolyte known in the art, which can be selected according to actual needs.
[0103] The secondary battery provided in the embodiment of the present application has both good electrochemical performance and high safety performance, especially high energy density and low thermal runaway risk. The secondary battery can be a lithium secondary battery or a sodium secondary battery.
[0104] The embodiment of the present application also provides an electric device, including the secondary battery provided in the embodiment of the present application. The electric device includes but is not limited to 3C electronic products, such as mobile phones, laptops, tablet computers, drones, wearable electronic devices, etc. The electric device may also include power vehicles, such as new energy vehicles, electric bicycles, etc.
[0105] The present application also provides an energy storage system, including the secondary battery provided in the fourth aspect of the present application. Due to the use of the secondary battery provided in the present application, the energy storage system can have good thermal stability and good safety performance.
[0106] In some embodiments of the present application, the energy storage system includes an energy storage device and a power converter, the energy storage device includes a containing cavity and the secondary battery contained in the containing cavity, the power converter is used to perform power conversion processing on the voltage and / or current, and input the changed voltage and / or current to the energy storage device, so that the energy storage device can meet the power requirements of the electrical equipment.
[0107] The technical solution of the present application is further illustrated by multiple embodiments below.
[0108] Example 1
[0109] 1) The substrate (specifically LiNi 0.836 Co 0.104 Mn 0.06 O2) is placed in a reaction chamber of an atomic layer deposition device filled with dry air and heated to a first preset temperature (specifically 250° C.).
[0110] 2) The first reaction raw material is introduced into the reaction chamber. Specifically, the A element source (specifically lithium tert-butoxide) is introduced four times, each time for 300 ms; the X element source (specifically trimethyl phosphate) is introduced twice, each time for 1200 ms; the E element source (specifically trimethyl aluminum) is introduced four times, each time for 300 ms. Different element sources are introduced between two adjacent times. After the first reaction time, an inert gas is introduced into the reaction chamber for cleaning.
[0111] 3) introducing a second reaction raw material (specifically O3) into the reaction chamber, and after reacting for a second time, introducing an inert gas into the reaction chamber for washing.
[0112] 4) The above steps 2) and 3) are recorded as one deposition cycle, and the deposition cycle is 44 cycles to obtain the positive electrode material.
[0113] Example 2
[0114] The method further comprises 5): transferring the reactant obtained in step 4) to a tubular furnace, and performing heat preservation treatment under an oxygen atmosphere, specifically, heat preservation at 500° C. for 5 hours, and naturally cooling to obtain a positive electrode material.
[0115] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples are provided.
[0116] Comparative Example 1
[0117] 1) The substrate (specifically LiNi 0.836 Co 0.104 Mn 0.06 O2) is placed in a reaction chamber of an atomic layer deposition device filled with dry air and heated to a first preset temperature (specifically 250° C.).
[0118] 2) introducing the first reaction raw material into the reaction chamber. Specifically, introducing the A element source (specifically lithium tert-butoxide) four times, each time for 300 ms; introducing the X element source (specifically trimethyl phosphate) twice, each time for 1200 ms. After the first reaction time, introducing an inert gas into the reaction chamber for cleaning.
[0119] 3) introducing a second reaction raw material (specifically O3) into the reaction chamber, and after reacting for a second time, introducing an inert gas into the reaction chamber for washing.
[0120] 4) The above steps 2) and 3) are recorded as one deposition cycle, and the deposition cycle is repeated 6 times to obtain the positive electrode material.
[0121] Comparative Example 2
[0122] The substrate Ni 0.836 Co 0.104 Mn 0.06 (OH)2 and LiOH·H2O were ground and mixed in an agate mortar at a molar ratio of transition metal element to Li element of 1:1.05, and the ground material was transferred to a tube furnace and sintered at 730°C for 10 h in an oxygen atmosphere (oxygen purity was above 99.9% and the oxygen flow rate was 200 mL / min) to obtain the positive electrode material LiNi 0.836 Co 0.104 Mn 0.06 O2.
[0123] Performance Testing
[0124] (1) Thermal analysis of the fully charged cathode material was performed using differential scanning calorimetry (DSC) and thermogravimetric mass spectrometry (TG / MS).
[0125] 1) Prepare positive electrode sheets using the positive electrode materials provided in the above different embodiments and comparative examples as positive electrode active materials. Specifically, the positive electrode material, the conductive agent (specifically AB) and the binder (specifically PVDF) are mixed in a mass ratio of 90:5:5, and the obtained mixture is added to a dispersant (specifically N-methyl-2-pyrrolidone, NMP) to obtain a positive electrode slurry. The positive electrode slurry is coated on a positive electrode current collector (specifically aluminum foil) to obtain a positive electrode sheet, which includes a current collector and a positive electrode active material layer disposed on the surface of the current collector.
[0126] 2) A metal lithium sheet is used as the negative electrode sheet and assembled together with the positive electrode sheet into a button-type half-cell in a glove box filled with argon gas.
[0127] 3) Each button half-cell assembled as above was charged to 4.3V at 1C constant current and constant voltage (constant voltage cutoff current was 0.05C), then disassembled in a glove box, the positive electrode sheet was taken out and soaked in a solvent (specifically dimethyl carbonate) for 1 hour, then rinsed with dimethyl carbonate (DMC) three times, and then the DMC on the surface of the positive electrode sheet was blown dry under an inert atmosphere. 5 mg of the positive active material layer was scraped from the pretreated positive electrode sheet to obtain each sample.
[0128] 4) Add sample and electrolyte (1 mol / L LiPF6 solution, solvent is ethylene carbonate and dimethyl carbonate with a volume ratio of 3:7) in a closed crucible at a ratio of 1 μL:1 mg, and perform DCS test. The atmosphere is Ar gas, the heating rate is 5°C / min, and the heating range is 30°C-450°C. The test results of the positive electrode materials of Comparative Examples 1 and 2 are summarized in Figure 8 middle.
[0129] 5) The sample was placed in an open crucible for TG / MS testing in an Ar atmosphere with a heating rate of 5°C / min in a heating range of 30°C-450°C.
[0130] (2) Morphology test
[0131] 1) Take the positive electrode material (powder) of each example and add it to anhydrous ethanol, ultrasonically disperse it to obtain a suspension, take a sample with a dropper and drop it onto an electron microscope grid covered with a support film, dry it, and observe its morphology using a FEI F20 field emission transmission electron microscope (TEM). The TEM photos of the positive electrode materials of Example 1 and Example 2 are shown in Figure 1. Figure 4 and Figure 5 shown.
[0132] 2) The positive electrode material (powdered) of each example was placed on the carbon conductive paste, and its morphology was observed using a German Zeiss Sigma scanning electron microscope (SEM).
[0133] (3) Elemental composition analysis
[0134] 1) Sample preparation: Take the positive electrode materials of each example respectively, mix the positive electrode materials, the conductive agent (specifically AB) and the binder (specifically PVDF) in a mass ratio of 90:5:5, add the obtained mixture into the dispersant (specifically N-methyl-2-pyrrolidone, NMP) to obtain a positive electrode slurry. The positive electrode slurry is coated on the positive electrode current collector (specifically aluminum foil) to obtain a positive electrode sheet, which includes a current collector and a positive electrode active material layer arranged on the surface of the current collector.
[0135] 2) Time of Flight Secondary Ion Mass Spectrometry (TOF-SIMS) test: The positive electrode sheet prepared above is placed in a TOF-SIMS instrument, and the sample surface (the surface of the positive electrode active material layer) is excited with primary ions to generate a very small amount of secondary ions, and data processing is performed. The ion mass and element composition in the positive electrode material are determined based on the different times that the secondary ions take to fly to the detector due to different masses. The TOF-SIMS results of Example 1 and Example 2 are summarized in Figure 9A-9B , Figure 10A-10B middle.
[0136] 3) X-ray photoelectron spectroscopy (XPS) analysis: The positive electrode sheet prepared above is sent to an X-ray photoelectron spectrometer to excite the solid surface (the surface of the positive electrode active material layer) through X-rays. After data processing, the elements on the surface of the positive electrode material are quantitatively and qualitatively analyzed. The XPS results of Example 1 and Example 2 are summarized in Fig.11 and Fig.12 middle.
[0137] (4) Phase analysis
[0138] The positive electrode materials of Example 1, Example 2 and Comparative Example 2 were tested in an X-ray diffraction instrument to obtain X-ray diffraction (XRD) spectra of the positive electrode materials.
[0139] (5) Electrochemical performance test
[0140] The button half-cells prepared in the above thermal analysis test were used as samples for cycle performance testing in a constant temperature box at 30°C. Specifically, the battery was charged to 4.3V at 1C constant current and constant voltage, with a constant voltage cutoff current of 0.05C, and then discharged to 2.5V at 1C constant current to perform charge and discharge cycles. The first cycle charge / discharge specific energy of the battery and the capacity retention rate after 100 charge and discharge cycles were calculated.
[0141] The results of elemental composition analysis of each sample are summarized in Table 1. The DSC test data of the closed electrolyte system and the results of the electrochemical performance test are summarized in Table 2.
[0142] Table 1
[0143]
[0144] Table 2
[0145]
[0146]
[0147] Combining the data in Table 1 and Table 2, it can be seen that the positive electrode material provided in the embodiment of the present application can significantly reduce the heat release of the lithium nickel composite oxide material in the electrolyte environment under the synergistic effect of the first shell layer and the second shell layer, and combined with the O2 gas production monitoring curve and the thermal weight loss curve of Example 1 and Example 2 during the heating process, it is fully demonstrated that the positive electrode material provided in the embodiment of the present application can avoid peak heat release by inducing the core material to release lattice oxygen, thereby greatly improving its thermal stability. In addition, the electrochemical performance test results show that the electrochemical performance of the positive electrode material provided in the embodiment of the present application is comparable to that of the material in the prior art, and even the 100-cycle capacity cycle retention rate is significantly better than that of the material in Comparative Example 2. Therefore, the embodiment of the present application provides a positive electrode material having both thermal stability and good electrochemical performance.
[0148] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A positive electrode material, characterized in that: It includes a core, a first shell layer and a second shell layer that are successively coated on the surface of the core; the core includes A(Ni 1-x M x )O2, where 0 < x < 1, and wherein A is Li and / or Na, and M is at least one of Co, Mn, Nb, Ta, V, Mo, W, and Zr; The first shell layer comprises A(Ni 1-x M x ) 1-a E a O2, where 0 < x < 1, 0 < a < 1, and E is at least one of Al and Mg; The second shell layer includes a compound having Li—O and XO bonds, and / or a compound having Na—O and XO bonds; X is at least one of B, P and Si.
2. The positive electrode material according to claim 1, characterized in that The thickness of the first shell layer is less than or equal to 10 nm.
3. The positive electrode material according to claim 1, characterized in that In the first shell layer, the content of the E element gradually decreases from the first shell layer toward the core.
4. The positive electrode material according to claim 3, characterized in that The thickness of the first shell layer is less than or equal to 1 nm.
5. The positive electrode material according to claim 1, characterized in that In the first shell layer, the content of the E element first increases and then decreases from the first shell layer toward the core.
6. The positive electrode material according to claim 5, characterized in that The thickness of the first shell layer is in the range of 1 nm to 10 nm.
7. The positive electrode material according to claim 5 or 6, characterized in that In the first shell layer, the distance between the peak position of the molar content of the E element and the surface of the inner core is 50%-80% of the thickness of the first shell layer.
8. The positive electrode material according to any one of claims 1 to 5, characterized in that 0<a≤0.1。 9. The positive electrode material according to claim 1, characterized in that Any 1 μm of the second shell 2 The thickness difference within the range is less than or equal to 6nm.
10. The positive electrode material according to claim 1, characterized in that Any 1μm 2 In the material of the second shell layer with an area of 1nm-5nm and a thickness, the molar content of the X element is in the range of greater than 0 to less than or equal to 13%.
11. The positive electrode material according to claim 1, characterized in that The surface layer of the second shell layer includes a plurality of closely packed nanoparticles, pores exist between adjacent nanoparticles, and the pore diameters of the pores are less than or equal to 1 nm.
12. The positive electrode material according to any one of claims 1 to 11, characterized in that: There is also a cross-composite layer between the first shell layer and the second shell layer, and the cross-composite layer includes the compound having Li—O and XO bonds and / or the compound having Na—O and XO bonds, and the E element.
13. The positive electrode material according to claim 12, characterized in that The thickness of the cross-composite layer is less than or equal to 2 nm.
14. The positive electrode material according to any one of claims 1 to 13, characterized in that: The A(Ni 1-x M x )O2 has a layered structure.
15. The method for preparing a positive electrode material according to any one of claims 1 to 14, characterized in that: include: The substrate is placed in a reaction chamber filled with dry gas, and the first reaction raw material and the second reaction raw material are introduced. After atomic layer deposition, a positive electrode material is prepared; wherein the first reaction raw material includes an A element source, an X element source and an E element source; and the second reaction raw material includes an O element source.
16. The preparation method according to claim 15, characterized in that: When the first reaction raw material is introduced into the reaction chamber, the A element source, the X element source and the E element source are introduced alternately.
17. The preparation method according to claim 15 or 16, characterized in that: The method also includes placing the reactants after the atomic layer deposition in an oxygen environment for heat preservation treatment.
18. A positive electrode plate, characterized in that: The positive electrode plate includes a current collector and a positive electrode active material layer arranged on at least one side of the current collector; the positive electrode active material layer includes the positive electrode material as described in any one of claims 1-14, or the positive electrode material prepared by the preparation method as described in any one of claims 15-17.
19. A secondary battery, characterized in that: The secondary battery comprises the positive electrode sheet and the negative electrode sheet as claimed in claim 18 , and a separator and an electrolyte located between the positive electrode sheet and the negative electrode sheet.
20. An electrical equipment, characterized in that: The electric device includes the secondary battery as claimed in claim 19.
21. An energy storage system, characterized in that: The energy storage system includes the secondary battery as claimed in claim 19.